Comprehensive rehabilitation in a patient with corpus callosum syndrome after traumatic brain injury: Case report. Issue 28 (10th July 2020) - Wu, Xiao-li; Liu, Li-xu; Yang, Ling-yu; Zhang, Tong
Abstract: Rationale: Corpus callosum syndrome is a rare consequence of traumatic brain injuries. We provide a case of a patient with typical corpus callosum syndrome following a traumatic brain injury, and demonstrate neural reorganization and significant neural regeneration after comprehensive rehabilitation, using diffusion tensor imaging fiber bundle tracking. Patient concerns: We found typical clinical manifestations of damage to the corpus callosum. Diagnoses, Interventions, and Outcomes: We diagnosed a Traumatic Brain Injury (diffuse axonal injury and rupture of corpus callosum). The patient underwent a comprehensive multifaceted rehabilitation program including drug therapy, integrated physical therapy, occupational therapy, acupuncture, music therapy, computer-aided cognitive rehabilitation training, transcranial magnetic stimulation, and hyperbaric oxygen therapy. This rehabilitation program resulted in greatly improved physical and communication ability. Lessons: Comprehensive rehabilitation can significantly improve the function of patients with corpus callosum syndrome and may cause neural remodeling, as seen on diffusion tensor imaging.